The Laplace-Beltrami operator, $\Delta\colon \Omega^{k}(M)\longrightarrow \Omega^{k}(M)$ is defined as $\Delta=d\delta + \delta d$ where $d$ is the usual exterior derivative and $\delta$ is the codifferential: $$\delta=(-1)^{m(k+1)+1}*d*$$ where $*$ is the Hodge operator, $\alpha \wedge *\beta= \langle\alpha,\beta\rangle \text{Vol}$.

I am trying to prove that if $f\in C^{\infty}(M)$, $\Delta f=-\sum_{i=1}^{m}\frac{\partial^2f}{\partial x_{i}^2}$.

I have tried to do this: $\Delta f=(\delta d)(f)$ and $$(\delta d)(f)=\delta\sum_{i=1}^{n}\frac{\partial f}{\partial x_{i}}dx_{i}.$$

Now, $*(\frac{\partial f}{\partial x_{i}}dx_{i})=(-1)^{i-1}\frac{\partial f}{\partial x_{i}}dx_{1}\wedge \cdots dx_{i-1}\wedge dx_{i+1}\wedge \cdots \wedge dx_{m}.$

Again, $$\begin{split} d \left((-1)^{i-1}\frac{\partial f}{\partial x_{i}}dx_{1}\wedge \cdots dx_{i-1}\wedge \cdots \wedge dx_{m}\right)&=(-1)^{i-1}\frac{\partial ^2 f}{\partial x_{i}^2}dx_{i}\wedge dx_{1}\wedge \cdots \wedge dx_{m}\\ &=\frac{\partial ^2 f}{\partial x_{i}^2}dx_{1}\wedge \cdots \wedge dx_{m} \end{split},$$ and $$*\left(\frac{\partial ^2 f}{\partial x_{i}^2}dx_{1}\wedge \cdots \wedge dx_{m}\right)=\frac{\partial ^2 f}{\partial x_{i}^2}.$$

In conclusion, I obtain that $\Delta f=(-1)^{m+1}\sum_{i=1}^{m}\frac{\partial ^2 f}{\partial x_{i}^2}$, instead of $-\sum_{i=1}^{m}\frac{\partial ^2 f}{\partial x_{i}^2}$.

Can someone help me finding the wrong step? Thanks in advance.


Note the ambiguity: when you write $\delta$, it's really $\delta :\Omega^k \to \Omega^{k-1}$. In the case for $\Delta = \delta d$, $\delta$ is adding on one forms and thus $k=1$. So

$$ \delta = (-1)^{m(k+1)+1} * d* = (-1)^{2m+1} *d*= - *d*.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.